(untitled) (Revista de Psicología, 2019)
The result of text understanding depends on the linguistic properties of the speech as well as the reader’s characteristics. The objective of this paper is to evaluate the influence of the previous knowledge in understanding general and specific expository texts. For it, two texts were given to novel and expert readers: one divulgation expository text and the other one specialized expository text, by comparing the summaries of both and the answers to questions as a measure of reading understanding. In both groups no significant differences were found regarding general text understanding, though a better performance of the expert group was attained regarding the disciplinarian text. Taking into account the grouping variable of subjects, these results should support the hypothesis by which prior knowledge would be the main explanatory factor regarding the yield difference between both groups.